Heterotopic Ossification in adults following a burn: A phenomenological analysis - Foster, N.; Kornhaber, R.; McGarry, Sarah; Wood, Fiona; Edgar, Dale (Pergamon Press, 2017)
© 2017 Elsevier Ltd and ISBI Heterotopic Ossification (HO) is a rare but severely debilitating complication after a burn. Despite there being literature of varying quality explaining the postulated pathological process, risk factors and treatment for HO, the individual experiences of adults diagnosed with HO following a burn, remains unreported. This study sought to explore and describe burn survivors’ experiences of HO to gain a greater understanding of the clinical needs for this unique patient population. A phenomenological inquiry of five men and one woman selected through purposeful sampling collected in-depth interviews analysed using Colaizzi's method of data analysis. Five emergent themes: (1) Early signs and symptoms, (2) Impact on the rehabilitation journey, (3) The role of the health care professionals (4) Loss of independence and an increased reliance on others and, (5) Learning to live with it: uncertainty, hope and adaptation. Eleven cluster themes were identified, highlighting the meaning of each emergent theme. These findings describe the significant impact the unique symptomology of HO had on the physical and psychosocial functioning of participants throughout the rehabilitation journey. Central to engagement in rehabilitation, is the participants’ desire for autonomy particularly in the domains of living independently and community re-integration.